Modern Türk Şiirinde Çarpıcı Bir İlişki : Elektriğe İlan-ı Aşk! - Akay, Hasan (Kitabevi, 2001)
Being one of the important topics in Modern Turkish poetry, electricity used to be considered one of the symbols representing modernity. This study is concerned with the ideas about social and psychological factors behind this current. The analyses are made on texts from Western literature and especially on the poems of Tevfik Fikret and a certain poet with the penname T. Meftunu.
A Striking Relationship in Modern Turkish Literature: Declaration of Love to Electricity
Keywords: Modern Turkish Poetry; Style; Modernity; Electricity